Can physical education state policies impact on youth’s health behaviors? A natural experiment study - Lizandra Barbosa da Silva; Maria Cecília Marinho Tenório; Clarice Maria de Lucena Martins; Caroline Ramos de Moura Silva; Rafael Miranda Tassitano (Revista Brasileira de Atividade Física e Saúde)
Since 2011 an educational policy promulgated that public schools from Pernambuco have had to offer physical education (PE) class in the same shift where students are enrolled. This study examined the impact of the implementation of an educational policy on PE offering and students’ participation, and whether health related behaviors could be moderated by PE participation. It was a natural experiment study performed with data obtained from two cross-sectional studies (2007 and 2012) of a sample (n = 715) of high-school students from Caruaru. PE offering was assessed by asking students if they had PE class and adapted questionnaire was used to assess health-related information. It was observed that before policy implementation, most of the students (♂: 72.4%; ♀: 69.0%) was not engaged in any PE class during the week. After policy implementation the proportion of students who had at least one PE class/week increased (♂: 68.7%; ♀: 68.9%). Having ≥1 PE classes was not associated with the amount of physical activity either before (♂: OR = 1.47 (95%CI: 0.78 – 2.76)); ♀: OR = 1.02 (95%CI: 0.61– 1.72) or after (♂: OR = 0.90 (95%CI: 0.51 – 1.58)); ♀: OR = 1.06 (95%CI: 0.63 – 1.80) policy implementation. Fruit consumption was the only health-related behavior associated to PE class (♂: OR = 1.55 (95%CI: 1.01 – 2.70); ♀: OR = 1.48 (95%CI: 1.02 – 2.10). PE offering and participation of students improved and it seems that implementation of new policies for PE might impact on students’ behaviors, although, regarding to some limitations, not sufficiently to impact on overall students’ health behaviors.